2019
DOI: 10.1590/1679-78255313
|View full text |Cite
|
Sign up to set email alerts
|

Hankel transformation method for solving the Westergaard problem for point, line and distributed loads on elastic half-space

Abstract: The Hankel transformation method was used in this work to determine the normal and shear stress distributions due to point, line and distributed loads applied to the surface of an elastic media. The elastic media considered in this study was assumed to be inextensible in the horizontal directions, and the only non-vanishing displacement component is the vertical component. Such materials were first considered by Westergaard as models of elastic half-space with alternating layers of soft and stiff materials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…To a limited extent, the studies in [16][17][18] can be an option of overcoming the above difficulties. Transformations and additional functions associated with basic dependences were considered.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…To a limited extent, the studies in [16][17][18] can be an option of overcoming the above difficulties. Transformations and additional functions associated with basic dependences were considered.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Transformations and additional functions associated with basic dependences were considered. In the problem considered in [16], the Hankel's transform was applied to the basic differential Cauchy-Navier equilibrium equation to reduce the problem to an ordinary differential equation. In the case of the argument functions, transitions are used as well, however, the ones between partial differential equations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Ike [37] also used Fourier integral transform method to obtain closed-form solutions to 2D elastic half-plane problems using Love stress function approach. Ike [38] used the Hankel transformation method to solve the closed-form Westergaard half-space problem for concentrated and line load. He distributed real loads acting on the surface of the Westergaard half-space.…”
Section: Introductionmentioning
confidence: 99%
“…He distributed real loads acting on the surface of the Westergaard half-space. Ike [38] found that the Hankel transform method is ideal for solving the problem because of the axisymmetric nature of the vertical point load at the origin of Westergaard halfspace problem and the simplification offered by the Hankel transformation for axisymmetric problems. The point load solution was then used as the integral kernel in [38] to develop line solutions and distributed real loads.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages and merits offered by the displacement and stress-based methods have led researchers to develop solutions to the governing equations of the displacement and stressbased methods. Such solutions, which satisfy the governing equations of the displacement and stress-based methods are called respectively displacement functions and stress functions [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Some displacement functions of the theory of elasticity are: Green and Zerna potential (harmonic) displacement function, Boussinesq displacement functions.…”
Section: Introductionmentioning
confidence: 99%